Auxilliary production expenditures as object of management accounting (Journal of Economic Research & Business Administration, 2016)
In modern production companies the following types of production can be differentiated: main production, auxiliary production and servicing production. Alongside with the main production, production enterprises often have auxiliary production, which both are a part of production activ- ity of the enterprise necessary for servicing of the main production and provision of uninterrupted manufacture and release of its products. How- ever, auxiliary production units do not only ensure stability and trouble- free operation of the organization by providing it with necessary services and material resources at their actual cost but also generate profit from auxiliary production units to third-party companies and individuals. To be able to form sufficient information necessary for preparation and making of effective managerial decisions in the area of optimization of the finan- cial result one should keep separate records of expenses and profits of the organization related to auxiliary production units.
Keywords: Auxiliary production; direct expenses; indirect expenses; calculation